The Influence of Human Resource Competency, Use of Information Technology, Government Internal Control System and Use of Siskeudes on Accountability of Village Fund Management in Sedati District - Ayonda Hayyuani; Muhammad Taufiq Hidayat (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The aim of this research is to examine the influence of human resource competence, use of information technology, government internal control system (SPIP) and use of SISKEUDES on accountability in village fund management, especially in villages in Sedati District. The method used in this research is a quantitative method with a population of 16 villages in Sedati District, while the sample is 9 villages in Sedati District. The test uses the Statistical Product and Service Solution (SPSS 22) application with multiple linear regression analysis, t test, f test and coefficient of determination (R2) test. The results of the research show that Human Resource Competency, Use of Information Technology, Government Internal Control System (SPIP) and Use of SISKEUDES have a significant positive effect on accountability in village fund management.